THE PSYCHOLOGICAL IMPACT OF LEADERSHIP ON WELL-BEING OF TEACHERS AND STUDENTS’ PERFORMANCE AT SECONDARY SCHOOL - Muhammad Bilal Saleem Cheema; Dr. Ismat Bano (International Journal of Contemporary Issues in Social Sciences, 2024)
This study investigates the cerebral impact of leadership on the well- being of preceptors and scholars' performance at secondary seminaries. exercising a mixed- styles exploration design, the study combines quantitative checks and qualitative interviews to exhaustively understand the dynamics at play. The population includes secondary academy preceptors and scholars from colorful seminaries within an civic quarter. A stratified arbitrary slice fashion was employed to insure different representation across different seminaries. Data were collected through formalized questionnaires assessing cerebral well- being and performance criteria , followed by in- depth interviews with a subset of actors to gain qualitative perceptivity. The findings reveal significant correlations between leadership styles and the cerebral well- being of preceptors, which in turn influence pupil performance. The study underscores the significance of effective leadership in fostering a probative educational ground.